Geomorphological study of chamical region (la rioja, argentina) as the basis for the analysis of natural hazards - Carina Seitz; Facundo Scordo; Paula Andrea Zapperi (Boletín Geográfico)
Chamical region is located in a semiarid morphoclimatic area. Its characteristic morphodynamic processes are fluvial and eolian. On the other hand the topographical and seismotectonic characteristics of the region lead to azonal modelers agents, such as gravity and seismic events, which do not depend on climate conditions. These processes are active currently in a state of constant evolution. The goal of this work is to develop a geomorphological map of the Chamical region.The morphoestructural units grouping different landforms, as well as the morphodynamic processes that gave rise to them, were demarcated. This map is an initial basic tool for risk assesment. Information was taken from geological maps 1: 250000 published by Geological and Mining Service of Argentina (SEGEMAR), SPOT images obtained from Google Earth and the 250 GIS data base of the National Geographic Institute (IGN). Morphostructural units grouping different landforms and morphogenetic processes were defined according to Demek criteria (1976). From the development of the geomorphological map of Chamical it was determined that the geomorphology of the area shows an important component of the endogenous tectonic morphogenetic process that resulted in the generation of mountain and valley systems. Currently, fluvial-wind processes shape a mountain landscape with fluvial valleys structurally controlled. To identify these processes, the use of images of Google Earth was very useful due to their high spatial resolution (SPOT multispectral images up to 2.5 meters) .Although the use of images has allowed to develop this work, the importance of validating the information through field work is recognized.